WT1 silencing by RNAi synergizes with chemotherapeutic agents and induces chemosensitization to doxorubicin and cisplatin in B16F10 murine melanoma cells - Zapata Benavides, Pablo; Manilla Muñoz, Edgar; Zamora Ávila, Diana Elisa; Saavedra Alonso, Santiago; Franco Molina, Moisés Armides; Trejo Ávila, Laura M.; Dávalos Aranda, Guillermo; Rodríguez Padilla, María Cristina (Spandidos Publications, 2012)
The Wilm's tumor gene (WT1), encoding a transcription factor that modulates the expression of certain genes that are involved in proliferation and apoptosis, is overexpressed in numerous solid tumors. WT1 is important for cell proliferation and in the diagnosis of melanoma. The objectives of this study were to investigate whether WT1 silencing is capable of synergizing with chemotherapeutic agents and whether this silencing is capable of sensitizing cancer cells to doxorubicin and cisplatin in the B16F10 murine melanoma cell line. In the present study, B16F10 cells were simultaneously treated with median lethal doses (LD50s) of WT1-1 or WT1-2 small hairpin RNAs (shRNAs) and chemotherapeutic agents. A total of 24 h posttransfection, a [3-(4,5-dimethylthiazol-2yl)-2,5- diphenyl tetrazolium bromide assay] MTT assay was performed. To determine whether shRNA interference (shRNAi) is capable of sensitizing B16F10 cells to chemotherapeutic agents, cells were transfected with an LD50 of each of the recombinant plasmids, treated with varying concentrations of doxorubicin or cisplatin 24 h post-transfection, and analyzed 48 h later for inhibition of cell proliferation using the MTT assay. We observed that WT1-RNAi and the two chemotherapeutic agents acted synergistically to inhibit B16F10 cell proliferation. The greatest inhibition of cell proliferation was observed with the WT1-2/cisplatin (91%) and WT1-1/cisplatin combinations (85%). WT1 silencing using shRNAi induced the chemosensitization of cells to doxorubicin and cisplatin, with the greatest inhibition (85%) of cell proliferation being observed in the cells treated with the WT1-2/cisplatin 6 ng/µl combination. Our results provide direct evidence that WT1 gene silencing has a synergistic effect with chemotherapeutic drugs and sensitizes B16F10 melanoma cells to doxorubicin and cisplatin. This suggests that these combination strategies are potentially utilized in melanoma therapy.